Lesser Trochanter Migration following Intramedullary Fixation of an Intertrochanteric Femur Fracture - Carlo Montoli; Cecilia Pasquali; Elia Paiusco; Vincenzo Pellecchia; Ettore Vulcano (Case Reports in Orthopedics)
Intertrochanteric femur fractures are commonly observed in the elderly and may be associated with a complete fracture of the lesser trochanter in over 50% of cases. The migration of the lesser trochanter secondary to the psoas muscle contracture is a rare event. This case report presents a rare case of sudden groin pain three-week status after intramedullary fixation of a intertrochanteric femur fracture.